Mapping Organizational Tensions Using KIPO in Federated Information Systems: A Case Study in a Brazilian Bank - Antonio, Nadja; Dias, Roberto; Malcher, Paulo; Horita, Flávio; Santos, Rodrigo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
The management of several information systems (IS) faces challenges with the number of existing, autonomous, distributed, and heterogeneous databases. By the need for an integrated access, these arrangements have been explored as federated IS (FIS). FIS are affected by several situations that generate tensions in their management. In order to discover these organizational tensions, a qualitative case study in a real context - bank credit - based on interviews was conducted with stakeholders of a real FIS. Next, we performed the scenario analysis with the data from the interviews and used the GUT Matrix tool to analyze and identify the tensions. Finally, a decision map to analyze and identify the tensions and an ontology, based on the Knowledge Intensive Process Ontology (KIPO), were used to map the tensions in the management of bank credit SIF. The results show that both the decision map and the developed ontology can be used as a practical tool to support practitioners in industry in the FIS management. As a contribution to the FIS area, this work presents another approach to support IS management focused on conceptual modeling and knowledge intensive process decisions. In addition, the developed ontology also allows the description of tacit knowledge to support FIS managers in the investigated context.